Meta-Analysis of Shrinkage Mode After Neoadjuvant Chemotherapy for Breast Cancers: Association With Hormonal Receptor - Zheng, Chun-Hui; Xu, Kai; Shan, Wen-Ping; Zhang, Ya-Kun; Su, Zhi-De; Gao, Xiang-Jin; Wang, Yu-Jue; Qi, Jian-Yu; Ding, Xiao-Yan; Wang, Chun-Ping; Wang, Yong-sheng (Frontiers in Oncology, 2022)
Patients with concentric shrinkage mode after neoadjuvant chemotherapy is considered to be ideal candidates for breast conserving treatment. While, what proportion of patients would represent CSM have not been well defined. This study was conducted to pool the rates of concentric shrinkage mode in patients undergoing NAC, determine the impact of receptor status on the shrinkage mode after NAC and estimate the rates of the CSM in various subgroups. We systematically searched the literature about shrinkage mode after NAC from PubMed, Web of Science, Embase, The Cochrane Library, CNKI, Wanfang database, Chinese science and technology journal full-text database published from 2002 to June 2020 on breast cancer shrinkage mode after NAC and carefully screened the literature by using eligibility criteria: (1)patients with primary breast cancer treated with NAC; (2) publications with available data of shrinkage mode measured by magnetic resonance imaging (MRI), or data of pathology and receptor status. The association between shrinkage mode and receptor status was estimated using Stata 15.1 software. This analysis included a total of 2434 tumors from 23 papers. The included studies were heterogeneous (I2=89.4%, P<0.01). Random effects model was used to estimate the overall rates of CSM: 56.6% [95%CI (50.5%, 62.7%)]. According to the analysis of receptor status, 10 of the paper was included for HR+ (hormone receptor positive)type analysis and the odds ratio of HR+ CSM was 45.7% [95%CI (36.4%, 55.0%)]; 9 of the paper was used for HR- type (hormone receptor negative) analysis and the incidence of HR-CSM is 63.1% [95%CI (50.0%, 76.1%)]; with HR+ type as the control, the OR of the HR- CSM rate is 2.32 (1.32, 4.08) ) folds of HR+ type. From subgroup analyses, the CSM% of luminal A, luminal B, Her2+, and triple negative were 29.7% (16.5%, 42.8%); 47.2% (19.1%, 75.3%); 59.0% ( 39.7%, 78.3%); 66.2% (52.8%, 79.6%), respectively.Breast cancer patients undergoing NAC did not get an ideal odds ratio of CSM. The incidence of CSM in breast cancer after NAC is associated with receptor status. Patients with triple-negative breast cancers have the highest rates of CSM after NAC.